Improvement of the Bioavailability and Glycaemic Metabolism of Cinnamon Oil in Rats by Liquid Loadable Tablets. (1st April 2012) - Han, Chunchao; Cui, Bo
Abstract : The purpose of this study is to investigate the bioavailability and glycaemic metabolism of cinnamon oil (CIO) carried by liquid-loadable tablets (CIO-LLTs), the carrier of a CIO self-emulsifying formulation (CIO-LS). The results of tests performed to evaluate the physical properties of the CIO-LLT complied with Chinese Pharmacopeia (2010). The release profile suggested that the CIO-LLT preserved the enhancement of in vitro dissolution of cio. After orally administration, the plasma concentration-time profile and pharmacokinetic parameters suggested that a significant increase (P < 0.0001 ) in the C max, AUC and F were observed in the CIO-LLT. The blood glucose and the HbA1c were significantly decreased in alloxan-induced hyperglycemic rats (P < 0.05, P < 0.01, resp.), while the level of insulin secretion was markedly elevated in alloxan-induced hyperglycemic rats (P < 0.05 ). The alloxan-damaged pancreatic β -cells of the rats were partly recovered gradually after the rats were administered with CIO-LLT 45 days later. CIO-LLT could improve the bioavailability and glycaemic metabolism of CIO.